COMMUNICATIVE APPROACH AS A CONFLICT REGULATION TOOL IN THE BUSINESS ENVIRONMENT (Development Service Industry Management, 2025)
The article provides a comprehensive analysis of the concept of conflict as an object of managerial interaction within the organizational environment. The author examines the historical evolution of theoretical approaches to understanding conflict, highlighting key paradigms such as the social-conflict theory, psychoanalytic theory, functionalism, interactionism, human needs theory, rationalist models, and the communicative approach. These theoretical perspectives reflect the transformation of scholarly views regarding the origins, nature, and implications of conflict in both societal and organizational contexts. The study also synthesizes existing definitions of the concept of "conflict," which enabled the formulation of an author's interpretation. Conflict is defined as a process that arises due to objective or subjectively significant contradictions between opposing interests, needs, values, or goals. It may manifest in various forms – including intrapersonal, interpersonal, or intergroup conflicts – and is typically accompanied by emotional tension, communicative or behavioral activity, and encompasses the full cycle of interaction, from underlying causes to resolution. Particular attention is given to communication as a critical determinant in both the emergence and constructive resolution of conflicts. The article proposes a comprehensive definition of "communication" as a multicomponent process of information exchange involving meanings, emotions, gestures, values, and symbols among individuals or groups. This process is carried out using both verbal and non-verbal means and includes essential elements such as encoding, decoding, feedback, context, and potential noise. Communication is portrayed as goal oriented, designed to facilitate mutual understanding, coordinate actions, influence behaviors, and establish sustainable social connections within specific situational contexts. Furthermore, the article presents a structured classification of the primary types of communication employed within enterprises, segmented by various criteria: direction of information flow, degree of formality, transmission method, communicative content, media type, interaction character, and level of engagement. The study's findings provide a theoretical foundation for enhancing conflict management practices and underscore the strategic importance of communication systems in organizational development and cohesion.
Keywords: conflict theories; conflict; conflict management; communication; communicative interaction